O planejamento estratégico pessoal da saúde como suporte para o planejamento individual - Marques, Andréa Rodrigues (2011)
Health is related to the growth of life quality and longevity, helping people to have equilibrium in all personal life areas. In this context, the actual study consists in to develop a Personal Health Strategic Planning Model, to establish or to improve individual health. The study was based on the Strategic Planning and the Planning Model of Estrada (2006); Personal Strategic Planning and Models of Personal Strategic Planning, which tells about the changeable variables of Health. The adopted work methodology was the qualitative research, with exploratory objective and exploratory character. The procedure design adopted for to collect data, from the technical point of view, was the biographic research. The theoretical analysis let to establish the main elements for the composition of the Personal Health Strategic Planning Model purposed. To improve the understanding of this study, the purposed model is composed on two types: biological and psychosocial. The first one is composed by three elements: clinical control, nutrition and fitness, and the second one is composed by the resilient concept (stress adaptive answer), which is divided on three types: academic, emotional and social. It was possible to see that the Personal Health Planning can contribute for the Health promotion and the sickness prevention, because it systematizes the elements of Health and its scientific technical recommendations, guiding people to have healthy habits.